2016
DOI: 10.1111/jan.13162
|View full text |Cite
|
Sign up to set email alerts
|

Understanding interprofessional collaboration in the context of chronic disease management for older adults living in communities: a concept analysis

Abstract: Interprofessional collaboration is a complex evolving concept. Key components of interprofessional collaboration in chronic disease management for community-living older adults are identified. Implications for nursing practice, education and research are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 50 publications
2
59
0
Order By: Relevance
“…Nurse practitioners play a key role in creating and sustaining interprofessional teamwork (Quinlan & Robertson, ). As part of their role on interprofessional teams, nurse practitioners must collaborate with patients and other professionals to develop, coordinate and implement effective care plans (Bookey‐Bassett, Markle‐Reid, Mckey, & Akhtar‐Danesh, ). By drawing on their holistic training and practice, nurse practitioners can bridge the medical and nursing frames of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse practitioners play a key role in creating and sustaining interprofessional teamwork (Quinlan & Robertson, ). As part of their role on interprofessional teams, nurse practitioners must collaborate with patients and other professionals to develop, coordinate and implement effective care plans (Bookey‐Bassett, Markle‐Reid, Mckey, & Akhtar‐Danesh, ). By drawing on their holistic training and practice, nurse practitioners can bridge the medical and nursing frames of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study students showed highest response towards roles and responsibilities subscale as compare to team work and collaboration, Which means that students had highest readiness for their roles and responsibilities as compare to team work and share learning with other healthcare students. As students response in another study that Inter-professional education; trust among team members; help students to improve collaboration and improve patient care as a result the understanding selfawareness and job satisfactions will increase (Bookey-Bassett et al, 2017). Teamwork and collaboration can be promoted among nursing and paramedical students with the special study program's that may have an impact upon the roles and responsibility subscale of readiness among nursing and paramedical students.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, respondents mentioned shared goals, communication, co-location, and comprehensive and seamless care. For the purposes of this study, we define “collaboration” to encompass the working together of different health professionals to achieve shared goals [59]. Respondents described IDPC teams as centered on client needs, and one respondent characterized the physician as the core of the team.

“ Different health professionals of different disciplines working together to better serve the client .”

“… number of allied health workers who are working alongside the physician… ”.

…”
Section: Resultsmentioning
confidence: 99%